2011
DOI: 10.1186/1471-2350-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in Chinese Hans with autosomal dominant polycystic kidney disease

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is the most common inherited renal disease with an incidence of 1 in 400 to 1000. The disease is genetically heterogeneous, with two genes identified: PKD1 (16p13.3) and PKD2 (4q21). Molecular diagnosis of the disease in at-risk individuals is complicated due to the structural complexity of PKD1 gene and the high diversity of the mutations. This study is the first systematic ADPKD mutation analysis of both PKD1 and PKD2 genes in Chinese patients us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…They are shown in Supplemental Table 2, with the scores established to evaluate their putative pathogenicity by different programs (see Methods). Six were previously reported, 10,[12][13][14][15] and three were present in our in-house database: p.Thr2710N and p.Arg3183Gln were associated with another PKD1 or PKD2 mutation in patients diagnosed in the fourth decade, and the p.R3277C mutation was identified at the homozygous state in a woman transplanted at 50 years. No additional PKD1 or PKD2 variations were identified in the other patients.…”
mentioning
confidence: 99%
“…They are shown in Supplemental Table 2, with the scores established to evaluate their putative pathogenicity by different programs (see Methods). Six were previously reported, 10,[12][13][14][15] and three were present in our in-house database: p.Thr2710N and p.Arg3183Gln were associated with another PKD1 or PKD2 mutation in patients diagnosed in the fourth decade, and the p.R3277C mutation was identified at the homozygous state in a woman transplanted at 50 years. No additional PKD1 or PKD2 variations were identified in the other patients.…”
mentioning
confidence: 99%
“…9 Li et al 10 found the mutation c.3623-3624 insGTGT in exon 15 of PKD1 using combined denatured high-performance liquid chromatography (DHPLC) and gene sequencing. Yu et al 11 detected a series of mutations in 65 autocephalous lineages. If all the exons of PKD1 and PKD2 were to be screened for mutations using amplification and sequencing, it would not only be difficult to design the primers and perform elaborate PCR methodologies, but also a large number of samples would be required.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these highly homologous pseudogenes has made genetic analysis of PKD1 challenging, thereby discrimination of these pseudogenes from PKD1 requires locus-specific amplification methods. Although some researchers performed denaturing high-performance liquid chromatography (DHPLC) and polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) to screen mutations in ADPKD for research and clinical purposes [17,18], direct sequencing is considered to be a better choice [18]. Recently, Tan et al proposed a novel LR PCR Sequencing Method [14].…”
Section: Discussionmentioning
confidence: 99%